The Use of the Fragiligraph for Analysis of Clot Fomation and Lysis - Rimon, A; Danon, D (Thrombosis and Haemostasis, 1966)
These experiments demonstrate that the Fragiligraph may be used for those blood coagulation tests usually performed in a diagnostic haematological laboratory. The reproducibility of the tests and the individual variations in different human plasma have been determined. In thrombolytic therapy, where adequate control of the fibrinolytic level in the patient’s blood is requested, the importance of a fast and convenient method for its estimation, in view of individual variations of activity among patients and differences in reactivity to the treatment, cannot be over-emphasised.